PENINGKATAN KEMAMPUAN BAHASA INGGRIS DASAR BAGI SISWA SDN 1 SAYAN UBUD MELALUI PROGRAM PELATIHAN INTERAKTIF - I Made Juliarta; I Gede Nika Wirawan; Widya Fhitri; I Gede Madriana (LOKATARA SARASWATI, 2025)
This service research aims to improve the basic English language skills of students at SDN 1 Sayan Ubud through the implementation of an interactive training program. The background of this research is based on the observation that although English is an important skill in the era of globalization, the level of mastery of basic English among elementary school students still needs to be improved, especially in areas that have the potential to become tourism destinations such as Ubud. This training program is designed with student-centered methods, integrating participatory activities, educational games, and the use of audio-visual media to create a fun and effective learning environment. This approach is expected to stimulate students' interest in learning English and accelerate vocabulary acquisition and basic comprehension. The implementation of the program involved the stages of planning, implementation, and evaluation. Data was collected through participatory observation, pre-test and post-test to measure students' comprehension improvement, as well as questionnaires to obtain feedback on the effectiveness of the program. The expected results of this program are significant improvements in students' cognitive and affective abilities related to English, which include mastery of basic vocabulary, ability to construct simple sentences, and confidence in communicating. It is hoped that this program can serve as a model for similar efforts in other schools to support language acquisition.